Estimating Shifts in Phenology and Habitat Use of Cobia in Chesapeake Bay Under Climate Change - Crear, Daniel P.; Watkins, Brian E.; Friedrichs, Marjorie A. M.; St-Laurent, Pierre; Weng, Kevin C. (Frontiers in Marine Science, 2020)
Cobia (Rachycentron canadum) is a large coastal pelagic fish species that represents an important fishery in many coastal Atlantic states of the U.S. They are heavily fished in Virginia when they migrate into Chesapeake Bay during the summer to spawn and feed. These coastal habitats have been subjected to warming and increased hypoxia which in turn could impact the timing of migration and the habitat suitability of Chesapeake Bay. With conditions expected to worsen, we project current and future habitat suitability of Chesapeake Bay for cobia and predict changes in their arrival and departure times as conditions shift. To do this we developed a depth integrated habitat model from archival tagging and physiology data from cobia that used Chesapeake Bay, and applied the model to contemporary and future temperature and oxygen output from a coupled hydrodynamic-biogeochemical model of Chesapeake Bay. We found that estimated arrival occurs earlier and estimated departure time occurs later when temperatures are warmer and that by mid- and end-of-century cobia may spend on average up to 30 and 65 more days, respectively, in Chesapeake Bay. By mid-century we do not expect habitat suitability to change substantially for cobia, but by end-of-century we project it will significantly decline and shift closer to the mouth of Chesapeake Bay. Our study provides evidence that cobia will have the capacity to withstand near term impacts of climate change, but that their migration phenology varies from year to year with changing temperatures. These findings emphasize the need to incorporate the relationship between fishes and their environment into how fisheries are managed. This information can also help guide managers when deciding the timing and allocation of a fishery.